Google Earth Engine: Planetary-scale geospatial analysis for everyone - Gorelick, Noel; Hancher, Matt; Dixon, Mike; Ilyushchenko, Simon; Thau, David; Moore, Rebecca (Remote sensing of environment, 2017)
Google Earth Engine is a cloud-based platform for planetary-scale geospatial analysis that brings Google's massive computational capabilities to bear on a variety of high-impact societal issues including deforestation, drought, disaster, disease, food security, water management, climate monitoring and environmental protection. It is unique in the field as an integrated platform designed to empower not only traditional remote sensing scientists, but also a much wider audience that lacks the technical capacity needed to utilize traditional supercomputers or large-scale commodity cloud computing resources. •Large-scale computing is ubiquitously available but requires expertise to use.•Earth Engine is a platform designed to make planetary-scale RS analysis easy.•A large catalog co-located with massive CPU allows for interactive data exploration.•Its speed and ease of use are accelerating scientific discovery.•Some processes, like recursion, are currently ill-suited for this architecture.